1997
DOI: 10.1007/bf01907352
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of the Citrus Brown Mite,Eutetranychus orientalis (Acari, Tetranychidae) as prey for nine species of phytoseiid mites

Abstract: Nine phytoseiid species were tested to evaluate their potential as predators of Eutetranycbus orientalis (Klein). Typhlodromus atbiasae Porath and Swirski, Amblyseius barkeri (Hughes) and Amblyseius olivi Nasr and Abou-Awad had a shorter developmental period than Typhlodromus transvalensis (Nesbitt). Typhlodromus athiasae and Amblyseius barker/showed the highest oviposition rates. Amblyseius olivi showed a low rate of oviposition although Typhlodromus transvalensis has not able to lay any eggs. Immatures survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
1
16
0
1
Order By: Relevance
“…Research into phytoseiids able to control E. orientalis densities is very extensive (Fouly 1997;Momen and El-Borolossy 1999;Rasmy et al 2003;Ibrahim et al 2005;Romeih et al 2005) but there have been no clear practical results. A promising phytoseiid species is Amblyseius swirskii (Athias-Henriot), which can also adequately develop feeding on E. orientalis Zaher et al 2007), and it is commercially produced and extensively used in greenhouses of southern Spain to control a variety of pests (Calvo et al 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Research into phytoseiids able to control E. orientalis densities is very extensive (Fouly 1997;Momen and El-Borolossy 1999;Rasmy et al 2003;Ibrahim et al 2005;Romeih et al 2005) but there have been no clear practical results. A promising phytoseiid species is Amblyseius swirskii (Athias-Henriot), which can also adequately develop feeding on E. orientalis Zaher et al 2007), and it is commercially produced and extensively used in greenhouses of southern Spain to control a variety of pests (Calvo et al 2009).…”
Section: Discussionmentioning
confidence: 96%
“…and Stethorus sp. have been reported as predators of Eutetranychus species in citrus of other parts of the world (Momen and El-Borolossy 1997;Smith et al 1997;Swirski et al 1967Swirski et al , 1970.…”
Section: Discussionmentioning
confidence: 98%
“…Fan and Petitt (1994c) reported that augmentative releases of N. barkeri provided control of broad mite, Polyphagotarsonemus latus Banks. It has also been reported to control spider mites (Karg et al 1987;Fan and Petitt 1994b;Momen and El-Borolossy 1997).…”
mentioning
confidence: 94%